الأسس النبوية في بناء العقلية الرشيدة دراسة حديثية تحليلية: Prophetic Principles of Developing Sound Rationality: An Analysis Based on Ḥadīth Studies - مَدْيَن جمال (الدراسات الإسلامية, 2022)
This article aims to explore the Prophetic principles of developing sound rationality. The sunnah of the Prophet contains numerous pearls of wisdom. The human mind is a primary tool to understand lived reality with all its fluctuations and complexities. Moreover, it is the first door to understanding the revealed texts. The Prophet’s sunnah provides many principles and rules that can be adopted to inculcate sound rationality in the personality of a Muslim. If one understands these Prophetic principles correctly and follows them properly, they will lead one to succeed in life with distinction, leadership, and brilliance. Islam is not against reason nor does it prohibit its use. This article aims at deriving the principles of developing sound rationality from the Prophetic sunnah and explaining them with examples.